Adverse Drug Reaction Monitoring Of Antipsychotics, Antidepressants And Mood Stabilizers In The Psychiatric Outpatient Unit Of A Teaching Hospital – A Retrospective Study - KINGSHUK LAHON; HARSHA M SHETTY; AMITH PARAMEL; GYANESHWAR SHARMA (International Journal of Pharma and Bio Sciences, 2012)
Adverse drug reactions (ADRs) are considered among the leading causes of morbidity and mortality. Antidepressants, antipsychotics and mood stabilizers are associated with adverse effects which can affect the compliance and course of treatment in mental disorders. Clinicians’ awareness about the adverse effects of psychotropic drugs and their preventability can foster rational and safe use of these medicines. There is a lack of studies addressing ADR monitoring activities in a mental health setting in India. The present study was therefore undertaken to monitor the ADRs of the antipsychotics, antidepressants and mood stabilizers in the psychiatric outpatient unit of our hospital. We wanted to study the prevalence and assess the causality, severity and preventability of ADRs of antipsychotics, antidepressants and mood stabilizers prescribed in our hospital. We did a retrospective analysis of case records of outpatient clinic of the department of Psychiatry of our hospital from 1st January 2006 to 31st December 2006. All patients diagnosed with psychiatric disorder as per ICD 10 criteria and receiving treatment with antidepressant/ antipsychotic/ mood stabilizer were included. Assessment of causality, severity and preventability of recorded adverse events was done using Naranjo’s scale or Drug interaction probability scale, modified Siegel and Hartwig Scale and modified Schumock and Thornton scale respectively. 115 ADRs were recorded in case records of 64 of the 222 patients who fulfilled the inclusion criteria. Psychotropic drug associated ADRs were similar to Western data, but prevalence is higher. Antipsychotics were the most common psychotropic drugs associated with ADRs. Weight gain, extrapyramidal symptoms and acid peptic disease were the most common ADRs and olanzapine, duloxetine and mirtazapine were the drugs causing maximum ADRs. ADRs were possible to probable, mild to moderately severe and some were probably preventable.